Case report: Acute kidney injury as the initial manifestation of chronic lymphocytic leukemia/small lymphocytic lymphoma - Bender, Sascha T.; Zeremski, Vanja; Wiech, Thorsten; Mertens, Peter R.; Gross, Christian (Frontiers in Medicine, 2023)
Chronic lymphocytic leukemia (CLL) is a lymphoproliferative disorder often diagnosed after incidental finding of leukocytosis. Renal involvement is usually clinically silent. Symptomatic renal impairment due to CLL/small lymphocytic lymphoma (SLL) cell infiltration in the kidney tissue is uncommon and acute kidney injury (AKI) as presenting feature is scarce. In this case report we describe a patient with AKI, due to CLL/SLL infiltration as presenting feature. Our report underlines the possibility of kidney injury as first evident symptom of CLL/SLL. Kidney biopsy is the mainstay in these cases to establish diagnosis. Treatment with zanubrutinib resulted in improved kidney function.